Determination of Crop Co-efficient Values for Jute (Corchorus olitorius L.) (The Agriculturists, 2018)
Site specific calibration of crop coefficient (Kc) values is essential for irrigation scheduling of any crop. In order to determine the values of Kc for jute, an experiment was conducted at the Irrigation and Water Management Division of Bangladesh Agricultural Research Institute (BARI), Gazipur. An improved jute variety BJRI Tosa-2 (O-9897) was used in this experiment. The study examined growth and yield of the jute in terms of four irrigation treatments distributed over 7-28 days intervals. The treatments were so designed that drainage was allowed between the consecutive irrigations. Irrigation at 14days interval produced the highest dry fiber yield (3.93 t/ha) and was considered to be suitable for estimating seasonal crop evapotranspiration and Kc values. The seasonal crop ET was 549.13 mm under this treatment. The Kc values of jute at initial, development, mid-season and late season stages were found to be 0.72, 1.39, 1.26 and 0.46, respectively. As there is no FAO-recommended Kc value for this crop, this locally calibrated values can be used for similar climatic conditions of Bangladesh and elsewhere. Therefore, based on Kc value, it can be recommended that jute can be irrigated by equal amount of water needed for crop evapotranspiration (ETc) for different growth stages (141.05, 142.57, 167.34, and 84.30 mm) to get maximum dry fiber yield.The Agriculturists 2018; 16(2) 115-122